Do ensino-aprendizagem da Álgebra ao ensino de equações polinomiais do 1º grau: representações múltiplas - Araújo Segundo, Salvino Izidro de (2012)
The present work deals with the difficulties, understanding and ownership of algebraic concepts by the students of primary school II, in the teaching and learning of polynomial equations of the first degree. Will be presented a bibliography on the history of teaching and learning of algebra, highlighted the need for a methodology for the classroom that focuses on knowledge construction, also will summarize the state of the art of research on teaching and learning of algebra, covering up the ideas of multiple representations as a tool that mediates the understanding, construction and acquisition of algebraic concepts, specifically the polynomial equations of the first degree. The path used in the development of investigative research was the educational research (Lankshear, Knobel, 2008), in which we operate as a research professor. The work of the classroom was developed in a class of Year 7 primary school, a public school in the Paraíba State, becoming the teaching-learning of polynomial equations of the 1st Degree in the context of multiple representations and problem solving.